Synchronization of gigapixel video streams on video walls - Drizhuk, D.D.; Poyda, A.A.; Godunov, A.I. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2013)
An approach and its software implementation for the visualization of video streams on multidisplay video walls of high resolution are described. The video streams are organized according to the principle of video pyramids (similar to image pyramids). The main attention is paid to the problems of synchronization of video tiles and to the user interaction with multinode systems.